Efforts to Improve The Understanding of Mathematics Concepts of Two-Dimentional Figures Materials Using Powerpoint Media in Primary Schools - Indah Cahyani (Universitas Sebelas Maret, 2020)
This article is intended to understand the mathematical concept of the two-dimentional figure data for the second grade students of elementary schools of Kalisari for the year of Caliology in 2020/2021. This study uses two cycles. Each cycle begins with planning, execution, observation, and reflection. The results of the study in first cycle showed 62% complete education and in second cycle an increase of first cycle, 81% students has complete among 21 education participants in the second cycle. The results showed that the PowerPoint media improved the understanding of the concept of students in Elementary School of Kalisari second grade level intangible architectural mathematical ability